Amino acid conjugated self-assembled molecules modified titanium surfaces - Türkaydın, Müge. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2019., 2019)
The goal of this thesis is to increase biocompatibility of titanium (Ti) surfaces, which is an extensively used biomaterial in medicine, by an easy and timesaving surface modification procedure. For this purpose, 3-aminopropyltriethoxysilane (APTES) molecule was conjugated by 3 different amino acids (histidine, leucine, and tryptophan). Newly synthesized molecules were used to form amino acid conjugated self-assembled monolayers on titanium surface. After modification of the surfaces by each of the amido amino acids, histidine and leucine amino acids were chosen to make up hydrophilic and hydrophobic regions on the surface and they were mixed with changing concentrations (v/v, 80:20, 50:50, 20:80). X-ray photoelectron spectroscopy (XPS) analysis and water contact angle measurements were performed for the characterization studies of all of the modified surfaces. Human osteoblast cells culture studies were performed on the surfaces, which were modified by this method aimed at improving the biocompatibility of titanium, in order to investigate cell viability on the modified surfaces.|Keywords : Titanium, Surface Modification, Self-assembled Molecules (SAMs), Amino Acids, Biocompatibility.
Keywords: Titanium.; Amino acids.; Biocompatibility.